The Influence of the Implementation of the Pancasila Student Profile Strengthening Project on the Improvement of Students' Adversity Quotient at SDN Parsanga II - Fajriyah, Fitri Nur; Ridwan, M; Asmoni, Asmoni (Electronic Journal of Education, Social Economics and Technology, 2025)
The Pancasila Student Profile Strengthening Project is one of the government's efforts to instill the noble values of Pancasila through eight core character traits used by educators to shape students' character, integrity, and competence. The adversity quotient serves as a bridge between the intelligence quotient (IQ) and emotional quotient (EQ), both of which are essential for daily life, especially in problem-solving. This study aims to measure the extent to which the Pancasila Student Profile Strengthening Project influences the adversity quotient, which plays a crucial role in shaping individuals to become more resilient and adaptive. This research adopts a mixed-methods design by sequentially combining quantitative and qualitative approaches to gain a deep and comprehensive understanding of the Pancasila Student Profile Strengthening Project and its impact on students' adversity quotient. The project has shown a positive influence on improving students’ adversity quotient, as evidenced by a questionnaire with an average score of 88.44 (N=25), indicating an increase in students' adversity quotient. This finding is also supported by the observed improvement in students' creativity and their ability to solve problems. The project has encouraged students to take on new challenges and become more aware of their surrounding environment.